2002
DOI: 10.1590/s1516-635x2002000100002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Nível de Lisina da Dieta e do Sexo Sobre o Desempenho e Rendimento de Carcaça de Frangos de Corte

Abstract: O experimento foi conduzido nas instalações da Faculdade de Medicina Veterinária e Zootecnia, UNESP, Campus de Botucatu, utilizando-se dois mil pintos de um dia de idade, da linhagem Ross, distribuídos em um delineamento inteiramente casualisado em esquema fatorial 2 x 2 (sexos x níveis de lisina) e criados até 49 dias de idade. As aves foram alimentadas com dietas: inicial (0-21 dias), crescimento (22-42 dias) e acabamento (43-49 dias), contendo 100% dos níveis de lisina recomendados pelo NRC (1994), ou 110% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 4 publications
1
7
0
12
Order By: Relevance
“…This is done by the earned value of the cuts and also by the quality demand and convenience in food preparation by the consumer. Thus, the breast becomes the most important section as it represents about 50% of the total protein of chicken (Almeida et al, 2002); with more ability to produce food derived as seasoned products, pre-cooked and frozen. Accordingly, for the creation of chickens after 49 days old, the Cobb 500 strain may become more attractive to the broiler industry integrators, since it obtained the lower feed intake and higher breast yield and breast meat when compared to the strains Ross 308 and Hubbard Flex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done by the earned value of the cuts and also by the quality demand and convenience in food preparation by the consumer. Thus, the breast becomes the most important section as it represents about 50% of the total protein of chicken (Almeida et al, 2002); with more ability to produce food derived as seasoned products, pre-cooked and frozen. Accordingly, for the creation of chickens after 49 days old, the Cobb 500 strain may become more attractive to the broiler industry integrators, since it obtained the lower feed intake and higher breast yield and breast meat when compared to the strains Ross 308 and Hubbard Flex.…”
Section: Resultsmentioning
confidence: 99%
“…In the production of commercial poultry strains intended for meat cuts, with the main objective of breast meat production, lysine is the principal amino acid to be handled in ration (Almeida et al, 2002; Araújo, 2001). Although lysine is not the first limiting amino acid for poultry, it is used as amino acid basis for calculating the optimal protein, as it is used almost exclusively for body protein synthesis and does not participate in metabolic interactions with other amino acids (Amarante Júnior et al, 2005;Meza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Com o objetivo de verificar esses níveis, Almeida et al (2002) não observaram diferença para ganho de peso, conversão alimentar e rendimento de carcaça quando utilizaram níveis de lisina acima do recomendado pelo NRC (1994) (100, 110 e 120% para as rações inicial, crescimento e terminação, respectivamente), porém observaram que os níveis mais altos de lisina resultaram em menores porcentagens de gordura abdominal quando comparados aos níveis mais baixos, nas fêmeas.…”
Section: Introductionunclassified
“…Likely, the lowest values of energy in the diet may have caused a lower deposition of muscular glycogen in relation to the control treatment as well as with the use of Rice Bran. On the other hand, Almeida et al (2002), studying the broiler diets, found no differences in the pH values of the breast at different slaughter ages. No influence of sex was found, supporting the findings by Lonergan et al (2003), Quentin et al (2003), Santos et al (2005) and Almeida et al (2002).…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, Almeida et al (2002), studying the broiler diets, found no differences in the pH values of the breast at different slaughter ages. No influence of sex was found, supporting the findings by Lonergan et al (2003), Quentin et al (2003), Santos et al (2005) and Almeida et al (2002). However, Faria et al (2009), reports differences between sex, with means of 5.89 for males and of 5.83 for females.…”
Section: Resultsmentioning
confidence: 92%